Accelerated coloration of electrochromic device with the counter electrode of nanoparticulate Prussian blue-type complexes. (1st May 2015) - Lee, Kyoung-Moo; Tanaka, Hisashi; Takahashi, Akira; Kim, Kyung Ho; Kawamura, Midori; Abe, Yoshio; Kawamoto, Tohru
Graphical abstract: Abstract: Improvement of the color-switching response of an electrochromic device (ECD) is achieved using nanoparticles of Prussian blue (iron hexacyanoferrate, FeHCF-NPs) and of zinc hexacyanoferrate (ZnHCF-NPs) using size-control of ZnHCF-NP by the nanoparticle classification. Using the centrifuge method, ZnHCF is classified into three groups with average particle sizes of 59 nm, 71 nm, and 214 nm. The maximum transmittance contrast Δ T max of a FeHCF/ZnHCF ECD is blue-to-colorless with -ca. 60%, irrespective of the ZnHCF-NP used. However, the response time for coloration of the ECD with the smallest ZnHCF-NPs is only 13% of that of other ECDs with the largest ZnHCF-NPs, although the response time of the electrode with the smallest ZnHCF-NP electrode remains 65 % and 79 % of the largest case for oxidation and reduction, respectively. Because the applied voltage is limited to avoid the side reaction in the coloration of the ECD, the acceleration of the electrochemical response by the downsizing of ZnHCF-NPs leads the drastic change in the coloration speed.